Jean Miélot, bilan et perspectives (Carte Romanze, 2018)
Cet article se propose comme une mise à jour bibliographique sur Jean Miélot, célèbre auteur, traducteur, copiste, actif entre 1448 et 1470 auprès des ducs de Bourgogne. Ce «bilan» permet en même temps d’ouvrir de nouvelles «perspectives» de recherches, notamment dans le domaine des éditions critiques de nombre de ses œuvres, toujours inédites.This article deals with Jean Miélot, famous author, translator, copyist, who was charged with “making books” for the Dukes of Burgundy between 1448 and 1470; it aims to update the bibliography of his activity (bilan, since 2010) and to suggest new “perspectives” for future research, particularly for critical editions of many of his works, still unpublished.
Keywords: Jean Miélot; manuscrits du XVe siècle; 15th Century manuscripts